Laudato Si’ and the Environment: Pope Francis’ Green Encyclical - Harun, Martin (STF Driyarkara - Diskursus, 2022)
Pope Francis’ Encyclical Laudato Si’ invites scholars of all sciences to a dialogue on the ecological crisis in order to find better solutions before it is too late. Thus it is not surprising that in this collection of essays twelve scholars in religious and social sciences respond to his much appreciated encyclical. Editor Robert McKim, emeritus professor of Philosophy of Religion at the University of Illinois, opens the discussion with a proposal of inquiry into the challenges posed by the ecological crisis and how the world religions can and have responded to it in providing guidance and inspiration, and in what they have accomplished both as entire religious traditions and on a micro-level through particular religious communities, and also in giving birth to new environmentally constructive practices and rituals.